Corpus Linguistics Today: A Qualitative Approach - MISNAWATI, Misnawati; NUR, Sahril; TAHIR, Saidna Zulfikar Bin (Politeknik Negeri Ujung Pandang, 2024)
Corpus linguistics, the study of language form and function using computerized corpora, involves collecting extensive electronic texts to analyze language usage. It serves various objectives: qualitative analysis, exploring nuances in language use, and quantitative analysis, identifying patterns in word usage and collocations. Corpus linguistics tracks language variation over time, aids language teaching, supports lexicography, and contributes to discourse analysis. Its evolution grew from the 1950s to the present day, marked by technological advancements and theoretical integration. The article underscores the significance of qualitative analysis in providing contextual insights into language use. The systematic creation of a corpus involves steps like text selection, data collection, preprocessing, annotation, and quality control. Various qualitative analysis techniques, from discourse analysis to lexical semantics, offer diverse perspectives for studying linguistic phenomena. This article provides a concise overview of corpus linguistics, its evolution, the importance of qualitative analysis, corpus creation, and qualitative analysis techniques.